Algebraic immunity of non-linear components of symmetric ciphers - Кузнецов, О.О.; Горбенко, Ю.І.; Білозерцев, І.М.; Андрушкевич, А.В.; Наріжний, О.П. (Radiotekhnika, 2017)
Methods for calculating the algebraic immunity of cryptographic Boolean functions and non-linear components (substitutions) of symmetric ciphers have been studied. The results of the comparative analysis of algebraic immunity of non-linear nodes of symmetric ciphers are given.